2011
DOI: 10.4103/0972-2327.85870
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological treatment of epilepsy

Abstract: Nonpharmacological treatment of epilepsy includes surgery, vagal nerve stimulation, ketogenic diet, and other alternative/complementary therapies, e.g., yoga, Ayurveda, electroencephalography (EEG) biofeedback technique, aerobic exercise, music therapy, transcranial magnetic stimulation, acupuncture, and herbal remedies (traditional Chinese medicine). Alternative therapies, despite the term, should not be considered as an alternative to antiepileptic medication; they complement accepted drug treatment. Alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
0
12
0
3
Order By: Relevance
“…These are a few of the factors that create the need and hence the pursuit for innovative compounds of plant origin with fewer redundant side effects. [11] Several reports are available regarding anticonvulsant activity of different plants and efforts for further exploration of their activity is still going on. [12] Indian traditional medicine system which offers many potential medicinal plants for epilepsy either in raw form or in the form of formulations.…”
Section: Introductionmentioning
confidence: 99%
“…These are a few of the factors that create the need and hence the pursuit for innovative compounds of plant origin with fewer redundant side effects. [11] Several reports are available regarding anticonvulsant activity of different plants and efforts for further exploration of their activity is still going on. [12] Indian traditional medicine system which offers many potential medicinal plants for epilepsy either in raw form or in the form of formulations.…”
Section: Introductionmentioning
confidence: 99%
“…[1011] Yoga is popular, acceptable to the majority and also generally held to be useful and beneficial by the patients. Earlier evidence suggests the usefulness of meditation (Sahaj Yoga) practice in patients with epilepsy and later studies have demonstrated evidence for the use of yoga (Asanas, breathing exercises, relaxation techniques and meditation) as an adjuvant in management of epilepsy, possibly through its influence on the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…26,27,28,29,30 All these procedures also influence hormonal and cerebral blood flow levels. 31,32,33,34 These all factors may lead to improve the cerebral function, enhance the alertness and concentration abilities especially the Shirodhara, the relaxing and anxiolytic actions for which are well established. In a study carried out on ADHD patients the Shirodhara procedure helped in decreasing the auditory and visual reaction time and increasing the attention span (when measured using an electronic vernier chronoscope).…”
Section: Managementmentioning
confidence: 99%